Freight-train derailment rates for railroad safety and risk analysis. (January 2017) - Liu, Xiang; Rapik Saat, M.; Barkan, Christopher P.L.
Highlights: Estimate freight-train derailment rates by three variables. FRA track class, method of operation and annual traffic density were found to affect derailment rates. The estimated derailment rates provide a basis for railroad safety and risk analysis. Abstract: Derailments are the most common type of train accident in the United States. They cause damage to infrastructure, rolling stock and lading, disrupt service, and have the potential to cause casualties, and harm the environment. Train safety and risk analysis relies on accurate assessment of derailment likelihood. Derailment rate – the number of derailments normalized by traffic exposure – is a useful statistic to estimate the likelihood of a derailment. Despite its importance, derailment rate analysis using multiple factors has not been previously developed. In this paper, we present an analysis of derailment rates on Class I railroad mainlines based on data from the U.S. Federal Railroad Administration and the major freight railroads. The point estimator and confidence interval of train and car derailment rates are developed by FRA track class, method of operation and annual traffic density. The analysis shows that signaled track with higher FRA track class and higher traffic density is associated with a lower derailment rate. The new accident rates have important implications for safety and risk management decisions, such as the routing of hazardous materials.